Las microfinanzas desde un punto de vista de la etnología económica - Vontrat-Lino, Eric (2008)
Peru constitutes a nation of "tiger microentrepreneurs" and a paradigm in microfinance industry in the world-wide scale. The analysis of the Peruvian case - parameters and determinants of the success of the model applied - indicates us the conceptualization and the configuration of the microfinance market distant of the model developed by Mohammed Yunus, considered like the founder of the "modern microfinance". The present work sets out to demostrate the Peruvian specificity through elements related to the field of the economic ethnology.